2015
DOI: 10.3389/fpls.2015.00739
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of lysine acetylation in strawberry leaves

Abstract: Protein lysine acetylation is a reversible and dynamic post-translational modification. It plays an important role in regulating diverse cellular processes including chromatin dynamic, metabolic pathways, and transcription in both prokaryotes and eukaryotes. Although studies of lysine acetylome in plants have been reported, the throughput was not high enough, hindering the deep understanding of lysine acetylation in plant physiology and pathology. In this study, taking advantages of anti-acetyllysine-based enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 48 publications
11
92
0
Order By: Relevance
“…S3) (Kac indicates the acetylated lysine, and * represents a random amino acid residue). Three of these motifs, enrichment of Y, H or F on the +1 position toward the C terminus appeared frequently as previously described (50,51). The motifs KacH, KacY, Kac*F and KacF were also reported in strawberry (50) Figure 2B).…”
Section: Enrichment Of Acetylation Sites In Phaeodactylum-previous Stsupporting
confidence: 74%
See 1 more Smart Citation
“…S3) (Kac indicates the acetylated lysine, and * represents a random amino acid residue). Three of these motifs, enrichment of Y, H or F on the +1 position toward the C terminus appeared frequently as previously described (50,51). The motifs KacH, KacY, Kac*F and KacF were also reported in strawberry (50) Figure 2B).…”
Section: Enrichment Of Acetylation Sites In Phaeodactylum-previous Stsupporting
confidence: 74%
“…Recent studies have found amino acid residue over-or under represented at particular positions surrounding the acetylated lysine site in plants (50,51) and bacteria (18,20,(52)(53)(54). In this study, we defined 17 significantly enriched acetylation site motifs from 1894 unique sites accounting for 81.5% of sites identified, namely LKacY, KacY, LKac, Kac*F, I*Kac*L, YKac, K****Kac, FKac, KacH, KacF, K***Kac, I*Kac, Kac*L, Kac*Y, KacW, K*****Kac, F**Kac (Figure 2A and supplemental Table S6), and they display distinct abundance (supplemental Fig.…”
Section: Enrichment Of Acetylation Sites In Phaeodactylum-previous Stmentioning
confidence: 99%
“…Proteins were extracted from somatic embryos using the method described previously (Fang et al, 2015; He et al, 2016). Briefly, the embryos were ground in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…PTM-104, PTM Biolabs, Inc.), performed at 4°C overnight with gentle shaking (Pan et al, 2014; Fang et al, 2015; He et al, 2016). The supernatant was then removed, and the beads were washed four times with NETN buffer and twice with ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation